2011
DOI: 10.1159/000335806
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Aspirin Therapy Decreases Blood Glucose Levels but Does not Prevent Type I Diabetes-induced Bone Loss

Abstract: Backgroud: Diabetes is strongly associated with increased fracture risk. During T1-diabetes onset, levels of blood glucose and pro-inflammatory cytokines (including TNFα) are increased. At the same time, levels of osteoblast markers are rapidly decreased and stay decreased 40 days later at which point bone loss is clearly evident. Inflammation is known to suppress bone formation and induce bone loss. Previous co-culture studies indicate that diabetic bone is inflamed and diabetic bone marrow is capable of enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Many studies documented that Aspirin can significantly decrease blood glucose level 16 which is in agree with our findings in this study. It is claimed that Aspirin can cause decrease in basal rates of hepatic glucose production, enhances tissue insulin sensitivity, decreases insulin clearance, and decreases oxidative stress in diabetic patients 17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…Many studies documented that Aspirin can significantly decrease blood glucose level 16 which is in agree with our findings in this study. It is claimed that Aspirin can cause decrease in basal rates of hepatic glucose production, enhances tissue insulin sensitivity, decreases insulin clearance, and decreases oxidative stress in diabetic patients 17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…The water was available ad libitum . The bottles were replaced every morning with fresh water or drug solution, and the residual volume of water in bottles was measured to assure that the mice drank the intended water volume [17], [18]. The treatment was initiated 48 hours after parasite inoculation, for 20 days at the doses indicated in each figure.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it was demonstrated that the use of a non-selective COX inhibitor (Ketorolac) led to a delay in the fracture healing, but on the 35th day, all fractures (control and test groups) showed union [ 29 ]. Simon and collaborators [ 30 ] also demonstrated in an animal model of a bone repair study that NSAIDs can be a negative interference during the early stages of fracture union, leading to a reduction of fracture callus mechanical properties when administered during the initial stages of healing is performed.…”
Section: Discussionmentioning
confidence: 99%